"I had to fight for my VBAC": A mixed methods exploration of women's experiences of pregnancy and vaginal birth after cesarean in the United States. Issue 2 (3rd December 2020) - Basile Ibrahim, Bridget; Knobf, M. Tish; Shorten, Allison; Vedam, Saraswathi; Cheyney, Melissa; Illuzzi, Jessica; Kennedy, Holly Powell
Abstract: Background: Vaginal birth after cesarean (VBAC) is safe, cost‐effective, and beneficial. Despite professional recommendations supporting VBAC and high success rates, VBAC rates in the United States (US) have remained below 15% since 2002. Very little has been written about access to VBAC in the United States from the perspectives of birthing people. We describe findings from a mixed methods study examining experiences seeking a VBAC in the United States. Methods: Individuals with a history of cesarean and recent subsequent birth were recruited through social media groups. Using an online questionnaire, we collected sociodemographic and birth history information, qualitative accounts of participants' experiences, and scores on the Mothers on Respect Index, the Mothers Autonomy in Decision Making Scale, and the Generalized Self‐Efficacy Scale. Results: Participants (N = 1711) representing all 50 states completed the questionnaire; 1151 provided qualitative data. Participants who planned a VBAC reported significantly greater decision‐making autonomy and respectful treatment in their maternity care compared with those who did not. The qualitative theme: "I had to fight for my VBAC" describes participants' accounts of navigating obstacles to VBAC, including finding a supportive provider and traveling long distances to locate a clinician and/or hospital willing to provide care. Participants cited support from providers, doulas, and peers as critical to their ability to acquire the requisite knowledge and power to effectively self‐advocate. Discussion: Findings highlight the difficulties individuals face accessing VBAC within the context of a complex health system and help to explain why rates of attempted VBAC remain low.